(3GdMeGjI GdhbJjI dMbhb GdedcjI GdacQjI (B:s (3OQGSI ebGQfI (B/s - (3YHO GdLHGQ, TgO Ndjds ((3HjQhJ (B:s (3efThQGJ Rjf GdMbhbjI,s, 2018)
(3jgOa gPG GdcJGH Edi GdJYQja HGdMeGjI GdhbJjI GdJj JhaQ MeGjI eHcQI dMbhb GdedcjI GdacQjI hJMUjfgG ef GdJYOj YdjgG ef bHd GdZjQ hjJe Pdc YHQ EYWGA UGMH Cj Mb ef Mbhb GdedcjI GdacQjI JbOje WdH Edi GdLgI GdeNJUI dEUOGQ Cj ef GdELQGAGJ GdhbJjI hGdJMaXjI GdeSJYLdI VO ef jYJOj Ydi Mbhbg hJchf gPg GdELQGAGJ PGJ WGHY hbJj dG jeS CUd GdMb GdeJfGRY Ydjg ef hEdi LGfH gPg GdMeGjI GdhbJjI dMbhb GdedcjI GdacQjI gfGdc MeGjI JeGQS hJfaP Ydi GdefGaP GdMOhOjI hJYO LRAG GdMeGjI GdhbJjI hgj GdMeGjI GdMOhOjI(B.s
(3GdCUd CWQhMI eGLSJjQ(B-(3LGeYI GdfgQjf, cdjI GdMbhb, (B2017.s
(3HHdjhLQGajI (B: (3UaMI (B373-392.s
Keywords: (3Mbhb GdJCdja hGdfTQs -- (3bhGfjf hJTQjYGJs -- (3GdYQGbs; (3GdYQGbs -- (3SjGSI hMcheIs